Transvenous lead extraction in conduction system pacing - Wijesuriya, Nadeev; Elliott, Mark K; Mehta, Vishal; Behar, Jonathan M; Niederer, Steven; Wilkoff, Bruce L; Rinaldi, Christopher A (Frontiers in Physiology, 2022)
Conduction System Pacing (CSP) delivered by His Bundle Pacing (HBP) or Left Bundle Pacing (LBP) are exciting novel interventions in the field of Cardiac Resynchronization Therapy (CRT). As the evidence base for CSP grows, the volume of implants worldwide is projected to rise significantly in the coming years. As such, physicians will be confronted with increasingly prevalent and vital issues arising in long-term follow up, including the management of infected, malfunctioning, or redundant CSP leads. Transvenous lead extraction (TLE) is the first-line option for removal of pacing leads when indicated in these circumstances. The evidence base for TLE in the context of CSP is still in its infancy. In this article, we first provide a brief overview of TLE. We then examine the data on the long-term performance of HBP leads. Next, we describe the features of the Medtronic Select Secure 3830 lead, and how experience of TLE of this lead in the paediatric population has informed our practice. Finally, we review the current evidence for TLE in HBP and LBP, and discuss how future studies can address gaps in our current knowledge.